Role and Challenges of Primary Sector in the Structural Transformation in Africa (IJAS Indian Journal of African Studies, 2022)
This paper examines the primary sector’s performance, preferment, and challenges in structural transformation in the African economy. A systematic research has been done with the help of secondary data by using United Nations Conference on Trade and Development(UNCTAD), EXIM Bank and World Bank reports. Being either under-developed or developing nations, the primary sector mostly dominates the majority of African countries, which indeed is vital for embarking on its autonomous growth. The empirical evidence suggests that other developing countries with a large reliance on the primary sector show a positive effect on the nation’s economic efficiency within the context of sustainable development, but a fundamental challenge in Africa’s sustainable development is reducing its rampant poverty. Most underdeveloped African economies aren’t able to devote the required skilled resources to their primary production. Africa faces a complex mix of developmental problems within the primary sector, which are vast and multifaceted. A few of these include- the challenge of lesser devotion towards resources to the primary production; challenges of crawling technological adaptations and dependency on traditional harvesting & irrigation methods; less cost-effective agricultural techniques of the contemporary era with respect to inexpensive & unskilled farmers, etc. These challenges as well as their concomitant trade-offs, have to be strategically addressed to improve the prospects for sustained growth and development.
Keywords: Primary Sector; Africa; Structural Transformation; Production; Natural Resource